Modelling students’ perception on factors influence acceptance of research related software using multi-criteria decision analysis (MCDA) methods - Mohamadali, Noor Azizah; Garibaldi, Jonathan (2011)
This paper presents a case study of modeling user acceptance of research related software using multi-criteria decision analysis (MCDA) methods. Evaluation of user acceptance is crucial because success or failure of any technology depends on the acceptance by the users of the technology. Although various models are available to address user acceptance factors, none discuss the formal methodology to assign importance to the factors. In this paper, we study the use of multi-criteria decision analysis (MCDA) methods, which we believe may be able to address this limitation. A case study is conducted to achieve two objectives. Firstly, to model our proposed evaluation framework of user acceptance using MCDA methods. Secondly, to compare various MCDA methods used to rank the factors. The results demonstrate that except for the FAHP () method, all other methods produced similar ranking of the global user acceptance factors. In terms of ranking of the sub-factors, all methods produced the same results except for the ‘average’ method. We conclude that MCDA methods can successfully be used in this context.